PP63 The Role of Ethnicity Concerning the Prevalence and Severity of Obstructive Sleep Apnoea in Severely Obese Patients. (10th September 2013) - Leong, W B; Arora, T; Jenkinson, D; Thomas, A; Punamiya, V; Banerjee, D; Taheri, S
Abstract : Background: The South Asian population is at increased risk of cardiovascular disease. South Asians residing in western countries also have increased risk of obesity and associated comborbidities compared to white European counterparts. We compared the prevalence and severity of obstructive sleep apnoea (OSA) along with comorbidities in South Asians and white Europeans with severe obesity. Methods: Data from consecutive patients attending a specialist weight management service were analysed. Self-reported age, gender and ethnicity were gathered. Medical history was obtained by a trained physician to determine the quantity of comorbidities. Objective measurements of blood pressure, body mass index (BMI), and apnea-hypopnea index (AHI) were also acquired for study purposes. Results: A total of 308 patients (72.7% women; 13% South Asian) were included with a mean age and BMI of 46 ± 12y and 49 ± 8Kg/m 2, respectively. South Asians had significantly increased prevalence of OSA compared to white Europeans (p = 0.017) and were more likely to have severe OSA (p = 0.015). South Asians had significantly higher median AHI (24/hr: interquartile range [IQR] 9.3–57.6 vs. 9/hr: IQR 3.4–26.6; p < 0.01), significantly lower minimum oxygen saturation (76%: IQR 64-84% vs. 83%: IQR 77-87%; p < 0.01) and spent a significantly greater amount of time <90% oxygen saturation (8.4%: IQR 1.0–24.3% vs. 2.4%: IQR 0.2–16.0%; p = 0.03). South Asians also had a significantly greater number of comorbidities (p = 0.02) and poorer glycemic control (HbA1c 7.4 vs. 6.3, p < 0.01) compared to white Europeans. South Asian ethnicity, independent of demographics, BMI, and cardiovascular comorbidities was an independent predictor of OSA β = 0.61 (SE = 0.19), p < 0.01. Furthermore, we confirmed other independent OSA risk factors, consistent with previous studies, including increasing age and BMI and male gender (all p < 0.001). Conclusion: Severely obese South Asians had significantly greater prevalence and severity of OSA versus white Europeans. OSA may contribute to increased cardiovascular risk in South Asians compared to white Europeans with severe obesity. Mechanisms mediating the observed associations between these ethnicities require further investigation.